Edukasi Manajemen Stres Menuju Lansia Sehat dan Bahagia - Sujianti, Sujianti; Suprihatiningsih, Trimeilia; Andika, Rhuly; Farkhah, Laeli (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The senior is someone aged 60 and over. Common mental health issues among the seniors include stress and depression. Stress is an inevitable part of daily life, especially due to changes that require adjustment. A healthy and stress-free senior person is everyone's hope and dream. Happiness is one of the keys to a long, healthy life. This activity aims to provide information on stress management. The activity took place on Friday, December 5, 2025, at the Adipala 1 Community Health Center in Cilacap. The activity focused on stress management education for the seniors, leading to a healthy and happy elderly population. The results showed that the majority of participants understood stress management by identifying stress causes, staying connected with others, staying active, avoiding unnecessary stress, resting, scheduling enjoyable activities, and adopting a healthy lifestyle.